Effect of Surface Decalcification With Hydrochloric Acid on the Determination of Estrogen Receptor, Progesterone Receptor, Ki67, and Human Epidermal Growth Factor Receptor 2 Expressions in Invasive Breast Carcinoma Based on Immunohistochemistry and Fluorescence In Situ Hybridization. Issue 4 (8th April 2023) - Ping, Wu; Xin, Rao; Li, Zhang; Yupeng, Chen; Fangling, Song; Caihong, Ren; Shun, Hu; Sheng, Zhang
Abstract : Background: Bone is the most common site of metastatic breast cancer (MBC). EDTA is often used to decalcify bony tissue samples to ensure the accurate assessment of antigenicity in MBC. It takes 24 to 48 hours to decalcify small bone tissues such as bone marrow, which is considered unacceptable given the priority that is often placed on the rapid processing of bone marrow trephine cores. Thus, an effective decalcification method that preserves genetic material is needed. Aim: We performed immunohistochemical studies on surface decalcification (SD) in breast tumors and evaluated the effect of SD on receptor status and human epidermal growth factor receptor 2 (HER2). Fluorescence in situ hybridization was performed on a subset of these tumors to establish a protocol for handling bone specimens for MBC. Materials and Methods: Forty-four cases of invasive breast tumors were studied. We compared the immunohistochemical expressions of estrogen receptor (ER), progesterone receptor (PR), Ki67, and HER2 between control tissue (nondecalcified) and parallel tissue subjected to SD with hydrochloric acid. We also evaluated the effect of SD on the fluorescence in situ hybridization expression of HER2. Results: Categorical decreases in ER and PR expression were identified in 9/31 (29.0%) cases without SD and 10/26 (38.5%) cases with SD. HER2 expression changed from equivocal to negative in 4/12 (33.4%) cases. Among the HER2-positive cases, all remained positive after SD. The most significant declines in immunoreactivity occurred with Ki67, with an average decrease from 22% to 13%. The average HER2 copy numbers were 5.37 and 4.76 in the control and SD groups, respectively, and the average HER2/CEP17 ratios were 2.35 and 2.08, respectively. Conclusions: Overall, SD is an alternative decalcification method in bony metastases to assess ER, PR, and HER2 in MBC.